Measles Vaccination among Children (12 to 23 Months) in IDPs Settlements of Khartoum State, Sudan - Elhadi, Fatima Elshikh; Ibrahim, Ibrahim Awad (International Journal of Child Health and Nutrition, 2015)
Objectives: To assess the coverage rate of measles vaccine among children 12 to 23 months old and causes behind non-immunization in Internally Displaced Persons (IDPs) settlements. Methods: A multistage cluster sampling, community-based, descriptive cross-sectional study was conducted in IDPs Settlements of Khartoum State, Sudan, in 2009. Questionnaires were collected from 210 children (12 to 23 months) old to determine the coverage rate and causes behind non-immunization with measles vaccine. Results: Almost one quarter (24.8%) of children was not vaccinated by measles and the coverage rate was 75.2%; most of them had a vaccination card (86%) which means a high documentation and verification of mothers answers and only 14% verified the immunization status of their children by memory. The major cause of none vaccination was because of the busyness of the mother to take her child for vaccination, which comprises 10% of the children, followed by 6.2% of children not vaccinated because their mothers give no reason for not vaccinating their children. There was evidence of a significant association (P-Value = 0.037) between education level of the mothers’ and numbers of children under five years in the family with the immunization of Measles. Conclusion: Coverage of measles vaccination among children aged 12-23 months in IDPs settlements in Khartoum state was reasonably acceptable. The most common reasons for non-immunization were that the caretakers were busy to take their children for vaccination and being unaware of need to return for measles vaccine. Apply a health promotion program and use of different comprehensive interventions to convince mothers to complete measles immunization and increases coverage rate, also plan and implement an effective health education program to increase the awareness of mothers on the importance of measles vaccination.